Back to the Future: Studying Cholera Pathogenesis Using Infant Rabbits - Jennifer M. Ritchie (American Society for Microbiology, 2010)
ABSTRACT Cholera is a severe diarrheal disease, caused by Vibrio cholerae, for which there has been no reproducible, nonsurgical animal model. Here, we report that orogastric inoculation of V. cholerae into 3-day-old rabbits pretreated with cimetidine led to lethal, watery diarrhea in virtually all rabbits. The appearance and chemical composition of the rabbit diarrheal fluid were comparable to those of the “rice-water stool” produced by cholera patients. As in humans, V. cholerae mutants that do not produce cholera toxin (CT) and toxin-coregulated pilus (TCP) did not induce cholera-like disease in rabbits. CT induced extensive exocytosis of mucin from intestinal goblet cells, and wild-type V. cholerae was predominantly found in close association with mucin. Large aggregates of mucin-embedded V. cholerae were observed, both attached to the epithelium and floating within the diarrheal fluid. These findings suggest that CT-dependent mucin secretion significantly influences V. cholerae’s association with the host intestine and its exit from the intestinal tract. Our model should facilitate identification and analyses of factors that may govern V. cholerae infection, survival, and transmission, such as mucin. In addition, our results using nontoxigenic V. cholerae suggest that infant rabbits will be useful for study of the reactogenicity of live attenuated-V. cholerae vaccines. IMPORTANCE Cholera remains a significant threat to populations in developing nations. Currently, there is no reproducible, nonsurgical animal model of cholera, the secretory diarrheal disease caused by Vibrio cholerae. We found that oral infection of infant rabbits with V. cholerae led to lethal, watery diarrhea in most rabbits. Using this disease model, we discovered a new role for cholera toxin (CT) during infection. This toxin not only caused secretory diarrhea but also profoundly influenced how V. cholerae associates with the intestine and how the pathogen exits from the host. Rabbits inoculated with V. cholerae that does not produce CT developed mild diarrhea, suggesting that this model may prove useful for generating improved live attenuated-V. cholerae vaccine candidates. Overall, our findings suggest that the infant rabbit model will enable pursuit of several new avenues for research on cholera pathogenesis, as well as serve as a vehicle for testing new therapeutics.